2015
DOI: 10.1007/s10995-015-1823-x
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Factors Associated with Initiation and Continuation of Exclusive Breastfeeding

Abstract: Several factors associated with disparities in continued EBF were identified. The application of the LCHD framework furthers understanding of the multiple and interacting risks associated with early discontinuation of EBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
2
15
0
3
Order By: Relevance
“…Resultados semejantes se describen en el trabajo de Kelsey R. y cols 8 , en donde se evaluó la intención de amamantar más allá de los 3 meses, lo cual estaba estrechamente relacionado con el tiempo de reinicio de las actividades laborales, por tanto las probabilidades de no cumplir la intención de amamantar era mayor en las madres que retornan al trabajo antes de los 3 meses (OR: 2,25, IC 95% 1,23-4,12), entre las 6 semanas y 3 meses (OR: 1,82, IC 95% 1,30-2,56), comparadas con las madres que retomaban vida laboral posterior a los 3 meses. Los resultados de Jennifer S. Pitonyak y cols 15 , señalaron que la permanencia de los lactantes con sus madres trabajando desde la casa, se asociaba a mayor adherencia a la LME al cuarto mes (p = 0,0001). Además, el apoyo por parte del empleador se asoció a la continuidad de LME al cuarto mes o más (p = 0,02).…”
Section: Discussionunclassified
“…Resultados semejantes se describen en el trabajo de Kelsey R. y cols 8 , en donde se evaluó la intención de amamantar más allá de los 3 meses, lo cual estaba estrechamente relacionado con el tiempo de reinicio de las actividades laborales, por tanto las probabilidades de no cumplir la intención de amamantar era mayor en las madres que retornan al trabajo antes de los 3 meses (OR: 2,25, IC 95% 1,23-4,12), entre las 6 semanas y 3 meses (OR: 1,82, IC 95% 1,30-2,56), comparadas con las madres que retomaban vida laboral posterior a los 3 meses. Los resultados de Jennifer S. Pitonyak y cols 15 , señalaron que la permanencia de los lactantes con sus madres trabajando desde la casa, se asociaba a mayor adherencia a la LME al cuarto mes (p = 0,0001). Además, el apoyo por parte del empleador se asoció a la continuidad de LME al cuarto mes o más (p = 0,02).…”
Section: Discussionunclassified
“…Depression may need further investigation as a predictor for breastfeeding initiation among HIV-infected mothers, as our findings showed a trend towards significance. Some studies in high income countries, have demonstrated negative associations between the presence of perinatal depression and breastfeeding behaviours including intention and initiation 49 as well as duration of overall and exclusive breastfeeding 50,51 , but other studies, also in high-income countries, have shown no effect of perinatal depression on breastfeeding behaviours 52 . The lack of an association between IPV and negative breastfeeding outcomes also requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For both uninfected and HIV-infected mothers, interventions for breastfeeding initiation would need to address structural barriers relating to employment or work-place and facilitators to breastfeeding continuation 55 . Early return to work is a known risk factor for early discontinuation of breastfeeding 50 . For HIV-infected moms specifically, interventions for breastfeeding initiation would require an additional focus on individual factors to improve coping with HIV and a new baby.…”
Section: Discussionmentioning
confidence: 99%
“…As such, these studies have almost exclusively analyzed breastfeeding as an explanatory factor or predictor of later health and psychosocial outcomes for the child. To date, there are very few breastfeeding studies that explicitly utilize life course theory to explain breastfeeding behaviors themselves [Pitonyak, Jessop, Pontiggia, & Crivelli-Kovach, 2016;Whipps, 2017]. There is no theoretical reason for this to be the case.…”
Section: Current Theoretical Framework In Breastfeeding Researchmentioning
confidence: 99%